(untitled) (Indonesian Economic Justice Review, 2024)
This paper investigates the economic justice challenges posed by urbanization in Indonesia, particularly regarding access to resources such as housing, healthcare, education, and employment. Indonesia’s rapid urbanization, driven by rural-to-urban migration and economic development, has led to the expansion of cities like Jakarta, Surabaya, and Medan. However, this urban growth has also created significant disparities in access to essential services and economic opportunities, particularly for low-income populations and marginalized communities. The paper examines the effects of urbanization on social and economic equity, focusing on issues such as affordable housing shortages, unequal access to healthcare, and educational disparities in urban slums. It analyzes the role of government policies, such as urban development programs and poverty alleviation initiatives, in addressing these challenges. The study also evaluates the impact of private sector involvement in urban development, considering whether urban expansion primarily benefits wealthier urbanites while excluding poorer residents. The findings suggest that while urbanization has generated economic growth, it has also deepened social inequalities, particularly in large cities. The paper concludes with recommendations for policies aimed at promoting more equitable urban development, including affordable housing projects, inclusive healthcare access, and policies that ensure fair wages and job opportunities for low-income urban workers.